"И доконцавъ с нимъ миръ до своего живота": on the Question of the Context of the Opava Meeting in 1289, its Participants and the Eternal Czech-Galician Union - Kozak, S. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2021)
The article covers the circumstances of the meeting that took place in Opava
in 1289 with the participation of the Czech king Wenceslaus II Přemyslid, Galician-
Volynian suzerain Lev Danylovych and some Polish princes. As the Polish
participants in the meeting are not named in the sources, there are still doubts in
historiography as to who they were. An attempt was made to substantiate the version
that one of the unnamed Polish participants in the meeting was Prince
Władysław I Łokietek of Piast dynasty. This assumption is based on an analysis
of the eventful context of the Opava meeting, which was part of the struggle for
the Cracow heritage, as well as the matrimonial and dynastic ties that played a
very important role in medieval international communication. It is noted that the
union of Wenceslaus II, Lev Danylovych and Władysław I Łokietek repeatedly
manifested itself shortly after the meeting in Opava and was based on existing
dynastic ties and the conclusion of new marriage agreements. At the same time,
the assumption that Prince Henryk IV Probus of Silesia may also have been present
at the talks cannot be completely ruled out, although this hypothesis is currently
less plausible. Lack of sources does not allow to definitively refute any of
the versions. It is concluded that the Opava meeting was one of the key episodes
of the Galician-Czech political union of the late XIIIth century and clearly
demonstrated how relevant international communication was in the struggle for
the Kraków throne. Lev Danilovych’s participation in the vicissitudes of the struggle
for the Kraków throne is considered to be inextricably linked with the orientation
towards an alliance with the Czech king and is connected with the
importance of an ally of the Galician-Volynian ruler ruling in Kraków. У статті висвітлюються обставини зустрічі, яка відбулась в Опаві у
1289 р. за участі чеського короля Вацлава ІІ Пршемисловича, галицько-волинського сюзерена Лева Даниловича та деяких польських князів. З огляду на те, що у джерелах польські учасники зустрічі не названі, в історіографії
досі існують сумніви щодо того, хто ними був. На підставі аналізу подієвого контексту опавської зустрічі, яка була складовою боротьби за краківську спадщину, а також матримоніальних та династичних зв’язків, які
відігравали дуже важливу роль у середньовічній міжнародній комунікації,
було здійснено чергову спробу обґрунтувати версію, що одним із неназваних
польських учасників зустрічі був саме лєнченський і сєрадський князь Владислав І Локєток із династії П’ястів. Це вважаємо ймовірним з огляду на
те, що союз Вацлава ІІ, Лева Даниловича та Владислава І Локєтка неодноразово виявляв себе невдовзі після зустрічі в Опаві та ґрунтувався на підставі існуючих династичних зв’язків та укладенні нових шлюбних угод.
Водночас, нами не відкидається повністю припущення, що на переговорах
міг також бути присутнім вроцлавський князь Генріх IV Пробус, хоч ця
гіпотеза наразі менш вірогідна. Брак джерел не дає змоги остаточно
спростувати жодну з версій. Зроблено висновок, що опавська зустріч була
одним із ключових епізодів галицько-чеського політичного союзу кінця ХІІІ ст.
і яскраво продемонструвала, наскільки актуальною в умовах боротьби за
краківський трон була міжнародна комунікація. Участь Лева Даниловича
в перипетіях боротьби за краківський трон розглянуто у невід’ємному зв’язку із орієнтацією на союз із чеським королем та пов’язувано із важливістю того, аби у Кракові правив союзник галицько-волинського володаря.